PENGARUH MODEL PROJECT-BASED INQUIRY LEARNING (PIL) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MATEMATIS SISWA SMP DI BALIKPAPAN - Tri Hariyati Nur Indah Sari; Husnul Khotimah; Suci Yuniarti (INSPIRAMATIKA, 2018)
The aims of this study are to examine students’ mathematical critical and creative thinking ability achievement in experiment and control group based on Project-Based Inquiry Learning (PIL). This study is quasi-experimental research with non-equivalent control group design. The whole students of eight grader in one of Public Junior High School in Balikpapan, Academic year 2018/2019 were selected as population. The sample for this study, two classes are taken as experiment class who get Project-Based Inquiry Learning (PIL) and control class who get conventional learning by using purposive sampling technique. The data of mathematical critical and creative thinking ability were analyzed by Mann Whitney non parametric test. The results of this study show that: (1) the ability of students’ mathematical critical thinking on Project-Based Inquiry Learning (PIL) classroom is not better than the conventional class; (2) the ability of students’ mathematical creative thinking on Project-Based Inquiry Learning (PIL) classroom is better than the conventional class